The Effects of Immigrant Consumption Experience Abroad in the Education of Albanian Consumption According to International Gusto and Standards - Elvira Fetahu; Ilir Bejtja; Elona Fetahu; Anila (Voci) Çekrezi (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
Going international for a national economy in an increasingly globalization process does not mean just thinking how to export products and services. First, you have to create and implement international standards for the home country products and services. The process of internationalization is an integral process, affecting culture, politics, economy and way of living as well. Going international for an economy is a very broad issue but the way we refer in this paper is very closely related to the living standards of the people and more specifically of the immigrant communities between the host country and the country of origin. There are different ways of rising up and establishing international standards in consumption in the domestic market, one of which sounds to be smooth and very natural considering the transformation process. Consumption is part of the culture and so is the way of living. This means that it should be a long process to adopt international standards of consumption in the internal market. But it is not the same when we consider immigrants and their relatives have intense exchange of experiences with them, and the fact that immigrants are bicultural. They naturally can 'import' their second culture elements and standards home. The positive effects of this phenomenon which comes as a result of the process of education of the domestic market from the immigrant consumption experience abroad directly impacts the home market demand for consumption according to the international gusto and standards. Albanian immigrant group have been for many years, and still are very important enclave for the internationalization of our economy, as they represent more than 1/3 of our total population. Having into consideration this fact, the goal of this paper is to analyze the consequences that the domestic market, goods and services, have had so far and how the production standards have evolved.
Keywords: F22; 330; internationalization; immigrant; consumption; bicultural; economy